Clinical, electrophysiological, and serological evaluation of patients with cramp-fasciculation syndrome - Poyraz, Mürüvvet; Matur, Zeliha; Aysal, Fikret; Tüzün, Erdem; Hanoğlu, Lütfü; Öge, Ali Emre (AVES, 2017)
Introduction: Cramp-fasciculation syndrome (CFS) is a rare peripheral nerve hyperexcitability syndrome. There are only a few reports on clinical and serological profile of a CFS cohort that was followed up by a single outpatient clinic. Methods: Clinical, electrophysiological, and serological features of 6 CFS patients (5 men, 1 woman; 27-65 years old) were investigated. Results: All patients presented with cramps, fasciculations, muscle pain, and autonomic symptoms, and 2 also reported numbness and burning sensation in limbs, suggestive of neuropathic pain. Antibodies to uncharacterized voltage-gated potassium channel (VGKC)-complex proteins were found in 2 patients and to contactin-associated protein-like 2 (CASPR2) in 1 patient. None of the patients had a tumor. Most of the patients revealed prolonged after-discharges following tibial nerve stimulation. Nerve conduction studies and R-R interval variability tests were normal, whereas sympathetic skin responses were increased in amplitude in 3 seronegative patients. Five patients showed favorable response to carbamazepine or pregabalin treatment, whereas 1 VGKC-antibody- positive patient was resistant to carbamazepine and immunosuppressant treatment. Conclusion: Neuropathic pain and VGKC-complex antibodies may be encountered in CFS patients. Although autonomic symptoms are commonly found in CFS, routine autonomic system tests which are done in electrophysiology laboratories might yield normal results.

Amaç: Kramp-fasikülasyon sendromu (KFS) nadir görülen bir periferik sinir hipereksitabilite sendromudur. Tek bir merkezden takip edilen KFS hastalarının klinik ve serolojik özelliklerinin bildirildiği az sayıda yazı vardır. Yöntem: Altı KFS (5 erkek/1 kadın, yaş aralığı: 27-65 yıl) hastasının klinik, elektrofizyolojik ve serolojik özellikleri incelendi. Bulgular: Bütün hastalarda kramp, fasikülasyon, kas ağrısı ve otonom belirtiler görülürken ikisinde ayrıca nöropatik ağrıyı düşündüren ekstremitelerde uyuşma ve yanma hissi mevcuttu. İki hastada tanımlanmamış voltaja duyarlı potasyum kanalı kompleks proteinlerine [voltage-gated potassium channel (VGKC)-complex proteins] karşı oluşmuş antikorlar, bir hastada “contactin-associated protein-like 2 (CASPR2)” antikoru bulundu. Hastaların hiçbirinde tümör yoktu. Tibial sinir stimülasyonu sonucunda hastaların çoğunda uzamış ard boşalımlar görüldü. Sinir iletim çalışmaları ve R-R interval değişkenliği testleri normalken seronegatif olan 3 hastada sempatik deri yanıtı amplitüdleri artmıştı. Beş hasta karbamazepin ve pregabalin tedavisine iyi cevap verirken VGKC-antikoru pozitif olan bir hasta karbamazepin veya immünsüpresyon tedavisine dirençli idi. Sonuç: Nöropatik ağrı ve VGKC-kompleks antikor birlikteliği KFS hastalarında görülebilir. Otonom belirtiler KFS’li hastalarda sık bulunmasına rağmen elektrofizyoloji laboratuvarlarında uygulanan rutin otonom sistem test sonuçları normal kalabilir.
Kramp fasikülasyon sendromlu hastaların klinik, elektrofizyolojik ve serolojik olarak değerlendirilmesi
WOS: 000404296300015
PubMed ID: 28680318
Keywords: Cramp-Fasciculation Syndrome (CFS); Peripheral Nerve Hyperexcitability; Voltage-Gated Potassium Channel (VGKC)-Complex Proteins; Neuropathic Pain; Kramp-Fasikülasyon Sendromu (KFS); Periferik Sinir Hipereksitabilitesİ; Voltaja Duyarlı Potasyum Kanal-Kompleks Proteinleri